SEM studies on focus and lepidonts of elasmoid scale of Cyprinus carpio communis L. as pollution indicator - Johal, M S; Ravneet, Ravneet (The Indian Journal of Animal Sciences, 2007)
Toxicological studies were carried out on the focus region and lepidonts present on the circuli of the elasmoid scale of Cyprinus carpio communis L. using scanning electron microscopy (SEM). Lepidonts are characteristic structures present on the circuli providing anchoring system to scale with the skin of the fish. The focus is the central part of the scale from where the scale starts its beginning. The meshwork in the focal region provides cushion like support and prevents it from mechanical injury. The circuli with lepidonts and focus got disorganized and lepidonts lost contact with skin when treated with two sublethal concentrations of 0.062ppm and 0.126ppm respectively. Progressive deterioration in the structure was observed, when these exposed fishes were put again in normal water for next 6Odays. However, it showed that organophosphate, monocrotophos if present in water has long term effects as residues and scale components like focal region and lepidonts on circuli can be used as pollution indicator.